2012
DOI: 10.5897/ajmr12.1511
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cryptosporidium and other intestinal parasites using different diagnostic techniques in Enugu Metropolis, South-Eastern Nigeria

Abstract: Cryptosporidium is a protozoan parasite and the aetiologic agent of a gastrointestinal disease, known as cryptosporidiosis. In this study, a total of 300 faecal samples were collected and analysed for the presence of Cryptosporidium, yeasts and other parasites using direct normal saline, iodine wet preparations, formol-ethylacetate concentration and modified Ziehl Neelsen staining techniques. Using direct normal saline and iodine wet preparation techniques, a total of 25(8.3%) samples out of 300 were positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Since cats shed only low numbers of oocysts (around 10 3 and 10 4 oocyst/g of feces), this technique may not be very sensitive in cats (Mekaru et al, 2007;Weber et al, 1991;Webster et al, 1996). In addition to its low sensitivity, this method needs an experienced scientist due to oocysts similarity to bacteria or yeasts in stool samples (Ukwa h and Ezeonu, 2013). Although serological techniques are more sensitive than the mi- croscopic methods, high costs, fa lse-positive reactions and no differentiation of active infection from past infection are considered as disadvantages (Doing et al, 1999;Frost et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Since cats shed only low numbers of oocysts (around 10 3 and 10 4 oocyst/g of feces), this technique may not be very sensitive in cats (Mekaru et al, 2007;Weber et al, 1991;Webster et al, 1996). In addition to its low sensitivity, this method needs an experienced scientist due to oocysts similarity to bacteria or yeasts in stool samples (Ukwa h and Ezeonu, 2013). Although serological techniques are more sensitive than the mi- croscopic methods, high costs, fa lse-positive reactions and no differentiation of active infection from past infection are considered as disadvantages (Doing et al, 1999;Frost et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Cryptosporidium infections in children and immune-compromised individuals such as HIVinfected persons have been reported from many parts of the world, including southwestern and midwestern Nigeria [4][5][6]8,10,[14][15][16]. This study was conducted in southeastern Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…Study realized by Adeniji, Sanni, Barimala, and Hart, (2007) found that banana contained low levels of antinutrients such as tannins, phytates, and oxalates. Ukwah, Ezeonu, Eze, and Uguru, (2014) reported that 10% banana peel powder significantly increased growth performance as compared to control. Utilization of banana flour can reduce the budget for feed in poultry sector.…”
Section: Discussionmentioning
confidence: 99%
“…Study realized by Adeniji, Sanni, Barimala, and Hart, (2007) found that banana contained low levels of antinutrients such as tannins, phytates, and oxalates. Ukwah, Ezeonu, Eze, and Uguru, (2014)…”
Section: Re Sultsmentioning
confidence: 99%